2022
DOI: 10.3390/ijerph19041935
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Wristbands in Exposure Assessment: Analytical Considerations and Comparison with Other Approaches

Abstract: Humans are exposed to numerous potentially harmful chemicals throughout their lifetime. Although many studies have addressed this issue, the data on chronic exposure is still lacking. Hence, there is a growing interest in methods and tools allowing to longitudinally track personal exposure to multiple chemicals via different routes. Since the seminal work by O’Connell et al. (2014), silicone wristbands (WBs) have been increasingly used to facilitate human exposure assessment, as using WBs as a wearable sampler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 138 publications
(345 reference statements)
0
21
0
Order By: Relevance
“…Silicone wristbands (SWs) have been adopted as promising wearable devices with monitoring capabilities [5–15] . Previous studies have demonstrated the relationships between phenol biomarkers found in urine and their corresponding residue on the wristband surface [5–7] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Silicone wristbands (SWs) have been adopted as promising wearable devices with monitoring capabilities [5–15] . Previous studies have demonstrated the relationships between phenol biomarkers found in urine and their corresponding residue on the wristband surface [5–7] .…”
Section: Introductionmentioning
confidence: 99%
“…SWs have emerged as promising external and noninvasive sampling devices in contact with the air and skin. They can passively estimate personalized exposure profiles captured in multiple microenvironments through dermal absorption or environmental pathways [8,11–13] . SWs are lightweight, convenient for human and animal participants to use, and can be mailed back and forth for analysis, admittedly with some loss of volatile species [14,15] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported associations between wristband concentrations and environmental exposures; for example, Paulik et al found that individuals living close to unconventional natural-gas drilling had higher concentrations than those individuals living farther away [ 21 ]. In addition to capturing short- and long-term exposures [ 20 ], silicone wristbands are minimally invasive to participants, easy to use, and stable for transport in hot and cold conditions [ 17 , 20 , 22 , 23 ]. Additionally, they can be partnered with demographic and location data to determine associations between potential chemical exposure and health outcomes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%